2022
DOI: 10.3390/vaccines10091502
|View full text |Cite
|
Sign up to set email alerts
|

Human Fc-Conjugated Receptor Binding Domain-Based Recombinant Subunit Vaccines with Short Linker Induce Potent Neutralizing Antibodies against Multiple SARS-CoV-2 Variants

Abstract: The coronavirus disease-19 (COVID-19) pandemic has been ongoing since December 2019, with more than 6.3 million deaths reported globally as of August 2022. Despite the success of several SARS-CoV-2 vaccines, the rise in variants, some of which are resistant to the effects of vaccination, highlights the need for a so-called pan-coronavirus (universal) vaccine. Here, we performed an immunogenicity comparison of prototype vaccines containing spike protein receptor-binding domain (RBD) residues 319–541, or spike p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…Therefore, developing new vaccines with more efficient immunogenicity highlights the necessity of further research in this area. Besides inducing neutralizing antibody, recombinant subunit vaccines have several advantages including high safety and yield as well as easy storage and transportation [11]. Studies have shown that RBD comprises of several immunodominant epitopes and therefore is a major target for neutralizing antibodies, which blocks the interaction of RBD-ACE2 and inhibits virus entrance to the host cells [24,[27][28][29], however, the immunogenicity of RBD is not strong enough.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, developing new vaccines with more efficient immunogenicity highlights the necessity of further research in this area. Besides inducing neutralizing antibody, recombinant subunit vaccines have several advantages including high safety and yield as well as easy storage and transportation [11]. Studies have shown that RBD comprises of several immunodominant epitopes and therefore is a major target for neutralizing antibodies, which blocks the interaction of RBD-ACE2 and inhibits virus entrance to the host cells [24,[27][28][29], however, the immunogenicity of RBD is not strong enough.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that RBD comprises of several immunodominant epitopes and therefore is a major target for neutralizing antibodies, which blocks the interaction of RBD-ACE2 and inhibits virus entrance to the host cells [24,[27][28][29], however, the immunogenicity of RBD is not strong enough. Using Fc domain of human IgG as a fusion partner has several advantages, including interaction with FcRn, increasing the half-life and stability of the fusion protein, binding to Fc receptor on immune cells and enhancing their immunological functions, enhancing immunogenicity by increasing uptake via FcγR by antigen presenting cells, and also efficient purification of the fusion protein by protein A-or G-affinity chromatography [11,[30][31][32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we used a Fc-linked trimeric spike RBD to improve the uptake and presentation of the trimeric spike RBD, and we used intranasal administration to achieve a more robust immunity in the upper airway. Twelve studies [ 29 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 43 , 44 , 45 ] have tried to use Fc-RBD subcutaneously or intramuscularly with mostly alum, one Freund’s, one MF59, manganese, or Montanide TM ISA720 adjuvants in mice, and one non-human primate model; but only one study has used intranasal vaccination in Balb/c mice, and it did not try to use it for boosting after priming with intramuscular inactivated vaccine.…”
Section: Discussionmentioning
confidence: 99%